Imperative situations: their features, structure and consistency (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the features, structure and consistency of imperative situations and their representation in Ukrainian language on the background of categorical semantics, structure and functionality of imperative.
Keywords: imperative; communicative situation; imperative situation; potential modality; subject of the will; addressee subject; executant subject